2001
DOI: 10.1038/sj.cr.7290063
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of the N-linked oligosaccharide structures on P-selectin glycoprotein ligand-1 (PSGL-1)

Abstract: PSGL-1, a specific ligand for P-, E-and L-selectin, was isolated from in vivo [ 3 H]-glucosamine labeled HL-60 cells by a combination of wheat germ agglutinin-agarose and P-or E-selectin-agarose chromatography. N-linked oligosaccharides were released from the purified, denatured ligand molecule by peptide: N-glycosidase F treatment and, following separation by Sephacryl S-200 chromatography, partially characterized using lectin, ion-exchange and size-exclusion chromatography in combination with glycosidase dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
(37 reference statements)
2
26
0
Order By: Relevance
“…The existence of SLe x -like moieties on O-linked glycans of PSGL-1 further supports this notion (5,6).…”
Section: Heparan Sulfate-like Proteoglycans Mediate Adhesion Of Humansupporting
confidence: 63%
“…The existence of SLe x -like moieties on O-linked glycans of PSGL-1 further supports this notion (5,6).…”
Section: Heparan Sulfate-like Proteoglycans Mediate Adhesion Of Humansupporting
confidence: 63%
“…CVA24v appears to bind to both ␣2,3-linked and ␣2,6-linked sialic acids, and this may at least partially explain why CVA24v causes respiratory disease more frequently than EV70, which mainly binds ␣2,3-linked sialic acid and almost exclusively causes ocular disease (50,53,76). On PSGL-1, the 3Ј-sialyl-TF trisaccharide is linked to either 3ЈSLN or sLe X , thus creating a disialic acid-containing glycan (2,72), which may provide even better binding to CVA24v. In agreement with this suggestion, we demonstrated recently that branched, disialylated glycans are functional receptors for another human ocular pathogen, Ad37, and showed that this soluble glycan was 200-fold more efficient in inhibiting Ad37 binding to corneal cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…PSGL-1 is a heavily O-glycosylated, mucinlike dimeric glycoprotein that is rich in serine/threonine repeat regions, with no less than 70 potential sites for O-glycosylation and only 3 potential sites for N-glycosylation on each subunit (17,63). The majority of the glycans on PSGL-1 are nonfucosylated, nonsialylated core 2 O-glycans, and thus, only a few of these structures contain sLe X (2,72). Here, we demonstrate that sLe X is present mainly on corneal cells but also on conjunctival cells and that soluble sLe X is a better inhibitor of CVA24v binding to corneal cells than sialic acid monosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic rolling assays conducted in the presence of a blocking anti-PSGL-1 mAb (KPL-1) indicated that PSGL-1-coated microspheres are still capable of tethering on E-but not P-selectin substrates (Goetz et al, 1997), supporting the notion that PSGL-1 has binding sites for E-selectin other than the crucial 19 amino acid sequence recognized by KPL-1. Along these lines, E-selectin appears to be capable of binding to N-linked oligosaccharides, including those found on PSGL-1 (Aeed et al, 2001;Patel et al, 1994;Vestweber, 1996). Taken altogether, E-selectin mediated tethering and rolling appears to involve additional as-yet-unidentified endogenous ligands distinct from PSGL-1.…”
Section: Introductionmentioning
confidence: 97%